Bioethics between quality and sanctity of life - Dyk, Wiesław (Studia Ecologiae et Bioethicae, 2003)
The aim of the article above is an attempt of the natural approach of based categories of bioethics, namely quality of life, the value of human life, and the sanctity of life (the quality of life makes its sanctity). By thorough analysis, in the biological aspect of goodness and evil and by study the emerging of rational and free (human) Being in the evolutional perspective the effort of showing of uniqueness, specificity, and immunity of a human person is undertaken. The analysis tends toward creating a basis for bioethical valuation. Bioethics as interdisciplinary science has to be based on interdisciplinary anthropology taking into account the ontic-existential structure of human beings.